(untitled) (MAUSAM, 1985)
INSAT-1A VHRR data have been used for a typical active monsoon situation over India which prevailed on 12/13 August 1982, to map the1emperature pattern over the Tibetan plateau region.. Gray shade and IR brightness values are analysed over the plateau and surrounding areas spatial and diurnal variations in the extent of the warm area and cloudiness are discussed. The plateau region is shown to be warmer than the surrounding which lends support to earlier theoretical and simulation studies.